2003
DOI: 10.1053/jlts.2003.50103
|View full text |Cite
|
Sign up to set email alerts
|

Clinical relevance of time of onset, duration, and type of pulmonary edema after liver transplantation

Abstract: We investigated the clinical significance of time of onset, duration, and type of pulmonary edema after orthotopic liver transplantation by retrospectively reviewing 93 consecutive recipients. Pulmonary edema was diagnosed by means of radiographic criteria and PaO 2 /FIO 2 ratio <300. Type was identified by pulmonary artery wedge pressure (hydrostatic, >18 mm Hg; permeability, <18 mm Hg O rthotopic liver transplantation is an accepted treatment for patients with end-stage liver disease. Survival after transpla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 27 publications
3
41
0
1
Order By: Relevance
“…A PaO 2 /FiO 2 ratio less than 200 mm Hg indicates severe deterioration of lung function early after transplantation and is frequently due to pulmonary edema. A similar finding was published before …”
Section: Discussionsupporting
confidence: 91%
“…A PaO 2 /FiO 2 ratio less than 200 mm Hg indicates severe deterioration of lung function early after transplantation and is frequently due to pulmonary edema. A similar finding was published before …”
Section: Discussionsupporting
confidence: 91%
“…Posttransplant ALI was associated with prolonged mechanical ventilation, an increased hospital stay, and graft failure. These data demonstrated a decreasing incidence of ALI and improved survival in comparison with earlier reports …”
Section: Anesthesia and Critical Caresupporting
confidence: 71%
“…Such values are an ominous sign in the immediate postoperative OLT period. Aduen et al 29 found that patients with PEs on chest radiography and PCPs <18 mm Hg have worse outcomes than those with PEs that are accompanied by PCPs >18 mm Hg (29% vs 0% mortality, respectively). Snowden et al 5 also noted that the presence of pulmonary infiltrate is suggestive of PE in patients undergoing OLT not only because of hydrostatic causes.…”
Section: Anesthesia and Analgesiamentioning
confidence: 99%